2008
DOI: 10.1094/mpmi-21-4-0396
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a New Locus, Ptr(t), Required for Rice Blast Resistance Gene Pi-ta–Mediated Resistance

Abstract: Resistance to the blast pathogen Magnaporthe oryzae is proposed to be initiated by physical binding of a putative cytoplasmic receptor encoded by a nucleotide binding site-type resistance gene, Pi-ta, to the processed elicitor encoded by the corresponding avirulence gene AVR-Pita. Here, we report the identification of a new locus, Ptr(t), that is required for Pi-ta-mediated signal recognition. A Pi-ta-expressing susceptible mutant was identified using a genetic screen. Putative mutations at Ptr(t) do not alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 40 publications
0
56
0
Order By: Relevance
“…Blue, red, and green color indicates the Piz-t alleles of southern, eastern, and northern regions, respectively. resistance phenotype (Jia & Martin 2008, Lee et al 2009). Transitions were more frequent than the transversions in all the Piz-t orthologs, comparable to earlier studies of plant genomes (IRGSP 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Blue, red, and green color indicates the Piz-t alleles of southern, eastern, and northern regions, respectively. resistance phenotype (Jia & Martin 2008, Lee et al 2009). Transitions were more frequent than the transversions in all the Piz-t orthologs, comparable to earlier studies of plant genomes (IRGSP 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, two NBS-LRR proteins within 50 kb, Pi5-1 and Pi5-2, were required for complete resistance (Lee et al 2009). At the Pi-ta locus, another gene Ptr(t) was found to be essential for Pi-tamediated resistance ( Jia and Martin 2008). The possible artificial selection of the large Pi-ta genomic region has been reported for maintaining the broad spectrum of Pi-ta-mediated blast resistance ( Jia 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Pi-ta has been effectively deployed in the United States and around the globe for controlling blast disease Jia et al 2000;Jia 2003;Jia et al 2004a,b;Huang et al 2008;Jia and Martin 2008;Wang et al 2008;Jia et al 2009a). Pi-ta encodes a predicted cytoplasmic protein with a centrally located NBS and a highly interrupted LRR domain (referred to as the LRD) at the carboxyl terminus that recognizes the corresponding avirulence gene AVR-Pita, triggering race-specific resistance.…”
Section: P Lant Resistance (R) Genes Have Evolved To Fightmentioning
confidence: 99%
See 1 more Smart Citation
“…Early reports indicated that the Pi-ta gene was introgressed into elite cultivars from landrace indica cultivars (e.g. Tetep and Taducan) for the control of infection by races of M. oryzae that contain AVR-Pita (Jia and Martin, 2008;Kiyosawa, 1967;Moldenhauer et al, 1990). Pi-ta locus has been effectively utilized to prevent blast disease for the past 40 years and is still effectively used in more rice cultivation areas (Kiyosawa 1967, Jia et al, 2004, Barman et al, 2004, Jia and Valent 2007.…”
Section: Discussionmentioning
confidence: 99%